THE EFFECT OF GRAIN STORAGE METHOD ON THE PRODUCTION OF QUALITY PRODUCTS (Academicia Globe: Inderscience Research, 2022)
The complexity of the organization of storage of large batches of cereals and cereals is associated with their physiological and physico-chemical properties. Grain is a living organism, in which various vital processes take place; the intensity of these processes is associated with the conditions of the external environment. If the external environment conditions have a good effect on the metabolism of grain cells, this will lead to a decrease in the quantity by worsening the quality of the unconditional grain.